The Foreign Policy Foundations of Trumpism - Joseph M. Humire (Norteamérica)
The election of President Donald J. Trump in 2016 introduced a new foreign policy, one that holds certain aspects of traditional schools of thought in international relations but is unique in that it does not prescribe to any one theory or academic framework. It does, however, contain foundational pillars that are essential to understand the cause and effect of President Trump’s foreign policy. Through careful review of President Trump’s prepared foreign policy speeches and interviews with Trump administration officials, this article argues that a return to nation-state sovereignty and burden sharing are the most important pillars of President Trump’s foreign policy, known as America First or “Trumpism.”